La aplicación de políticas contables y su incidencia en los estados financieros de la camaronera Villamar del cantón Huaquillas. - Torres Jara, Angel Stalin (My University, 2019)
The purpose of this research work is to know if the Villamar Shrimp Company has previously established accounting policies or not, in addition to identifying the different shortcomings in terms of the company's problem, which is the inefficient application of accounting policies and the impact that it causes Prepare the financial statements, especially knowing what accounting treatment they apply to the different accounts and based on what regulations define each treatment. Applying accounting policies in a company based on an accounting regulation is of great importance and impact, because if companies apply them by establishing an adequate accounting treatment for each accounting item for both the Balance of Financial Position and the Statement of Profit and Loss at the time to prepare the financial statements they generate a faithful representation and with that they reflect that such entity complies with the accounting standards required by law, in this way it represents that it maintains efficient control and therefore demonstrates reliability and integrity in the different accounting items that make up the statements Financial Most companies omit the application of accounting policies despite having the accounting treatment assigned for each account and others are based on particular models of accounting policies without considering whose models are developed and applied based on the size and magnitude of each company. Therefore, in this case study, I focus on identifying the accounting treatment that Shrimp Villamar applies to its different accounts, which should be stressed that it is a civil society and according to the law is not required to accept or adopt IFRS for which a visit was made to the company to collect information and learn about the weaknesses that arise corresponding to the application of accounting policies, which allowed establishing methods such as the deductive and field work where the technique was used interview to know in depth the treatment applied to its different accounting items, however, it was possible to verify the shortcomings that this company deals with, in the first instance that it does not have a previously established accounting policy manual, secondly that despite being a civil society refers to a particular model of accounting policies applied based on not IFRS for SMEs to apply accounting treatment in a superficial manner to several accounts because, in comparison with what is established in the IFRS for SMEs, it does not comply at all with respect to the initial recognition, initial measurement and subsequent measurement of each of the accounting items that They were analyzed, which also used bibliographic research that emphasizes different concepts of scientific articles that enrich and support the accounting treatments that should be applied to each account of the financial statements. Where a comparative chart is established to analyze the accounting treatment corresponding to the reality of the company against what is established in the IFRS for SMEs regulations, where as reflected results it was possible to identify that the Shrimp Villamar does not have an efficient control over the application of an accounting treatment adequate of their accounts and also that they violate the principle of uniformity since if they apply IFRS for SMEs as they express it, it must be for all their accounting items or simply not to apply but also for all their accounts and in accordance with the Accounting Principles Generally Accepted Regarding the findings found, it is suggested that Shrimp Villamar Identify the accounting items of greater control through a fully established account plan and can establish an adequate accounting treatment that helps efficient control, so that when preparing the financial statements they represent a greater level of reliability and integrity of their accounts and that such values be a faithful representation of the economic and financial activity of the company, in order to provide clear and concise information for interested parties and can contribute to good decision making.
El presente trabajo investigativo tiene como plena finalidad conocer si la Camaronera Villamar cuenta o no con políticas contables previamente establecidas, además de identificar las diferentes falencias en cuanto a la problemática de la empresa que es la ineficiente aplicación de políticas contables y el impacto que ocasiona al elaborar los estados financieros, especialmente conocer cuál es el tratamiento contable que aplican a las diferentes cuentas y con base en qué normativa definen cada tratamiento. Aplicar políticas contables en una empresa con base en una normativa contable es de gran importancia e impacto, porque si las empresas las aplican estableciendo un tratamiento contable adecuado para cada partida contable tanto para el Balance de Situación Financiera como el Estado de Pérdidas y Ganancias al momento de elaborar los estados financieros generan una representación fiel y con ello reflejan que tal entidad cumple con los estándares contables exigidos por ley, de esta forma representa que mantiene un control eficiente y por ende demuestra confiabilidad e integridad en las diferentes partidas contables que integran los estados financieros. La mayoría de las empresas omiten la aplicación de políticas contables a pesar de contar con el tratamiento contable asignado para cada cuenta y otras se basan en modelos particulares de políticas contables sin considerar que cuyos modelos están elaborados y aplicados en base al tamaño y magnitud de cada empresa. Por lo consiguiente en el presente estudio de caso se indago enfocándose en identificar cual es el tratamiento contable que la Camaronera Villamar aplica a sus diferentes cuentas, la cual cabe recalcar que es una sociedad civil y de acuerdo a la ley no está obligada a acogerse ni adoptar NIIF para lo cual se hizo una visita a la empresa para recolectar información y conocer las falencias que se presentan correspondiente a la aplicación de políticas contables, con lo cual permitió establecer métodos como lo son el deductivo y trabajo de campo donde se empleó la técnica de entrevista para conocer a profundidad el tratamiento aplicado a sus diferentes partidas contables sin embargo se pudo constatar las falencias con las que lidia esta empresa, en primer instancia que no cuenta con un manual de políticas contables previamente establecido, en segundo punto que a pesar de ser una sociedad civil hace referencia a un modelo en particular de políticas contables aplicado en base a normativa NIIF para Pymes para aplicar el tratamiento contable de manera superficial a varias cuentas porque comparado realmente con lo que establece la normativa NIIF para Pymes no cumple en lo absoluto referente al reconocimiento inicial, medición inicial y medición posterior de cada una de las partidas contables que se analizaron, con lo cual también se empleó la investigación bibliográfica donde se hace énfasis a diferentes conceptos de artículos científicos que enriquecen y respaldan los tratamientos contables que se debe aplicar a cada cuenta de los estados financiero. Donde se establece un cuadro comparativo para analizar el tratamiento contable correspondiente a la realidad de la empresa contra lo que establece la normativa NIIF para Pymes donde como resultados reflejados se pudo identificar que la Camaronera Villamar no tiene un eficiente control sobre la aplicación de un tratamiento contable adecuado de sus cuentas y además que incumple el principio de la uniformidad ya que si aplica NIIF para Pymes como según lo expresan debe ser para todas sus partidas contables o simplemente no aplicar pero así mismo para todas sus cuentas y rigiéndose en los Principios de Contabilidad Generalmente Aceptados. Referente a los hallazgos encontrados se sugiere que la Camaronera Villamar Identifique las partidas contables de mayor control mediante un plan de cuentas plenamente establecido y pueda establecer un tratamiento contable adecuado que ayude a el control eficiente, de tal forma que al elaborar los estados financieros representen un mayor nivel confiabilidad e integridad de sus cuentas y que tales valores sean una representación fiel de la actividad económica y financiera de la empresa, para así brindar información clara y concisa para las partes interesadas y puedan contribuir a una buena toma de decisiones.
Keywords: POLÍTICAS CONTABLES; TRATAMIENTO CONTABLE; PARTIDAS CONTABLES; ESTADOS FINANCIEROS